PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR MENGGUNAKAN MODEL PEMBELAJARAN INVESTIGASI KELOMPOK SISWA KELAS XI SMA NEGERI 1 BANTAENG : Improving the Ability to Write Procedural Texts Using A Group Investigation Learning Model for Students in Class Xi SMA Negeri 1 Bantaeng - Nurfadilah; Mayong; Idawati (Journal of Applied Linguistics and Literature, 2025)
This study is a Classroom Action Research which aims to determine the improvement of the ability to write procedural texts using group investigation learning model of class XI students of SMA Negeri 1 Bantaeng. The subjects in this study were students of class XI IPS 2 consisting of 13 students and 20 female students. The data were obtained using the procedure text writing test. The data analysis technique is using quantitative and qualitative techniques. The results showed that previously in the first cycle, the students' ability to write procedural texts was still minimal due to the lack of understanding of the material. Then, in the second cycle the students were able to determine the theme by collecting essay or reading materials, adjusting the topics that they could develop in the procedure text, and developing the essay outline into a correct and clear instruction. The implementation of the learning process of writing procedural texts using the group investigation learning model of class XI students of SMA Negeri 1 Bantaeng has improved which can be seen in the implementation of the second cycle students are more enthusiastic in participating in learning which is marked by the number of students who dare to ask questions, answer questions and express their opinions